Towards More Fluid Inclusion: Making Geoscience Undergraduate Degrees a Place of Belonging for All - Bethany R. S. Fox; Rukhsana R. Din; A. C. Davidson; Vicki Trowler; Victoria Ayodeji; Francisca Rockey; Manju Patel-Nair (Earth Science, Systems and Society)
Geosciences are central to addressing many of the challenges facing our society and environment today, and geoscience undergraduate degrees can lead to influential and lucrative careers in a range of fields. However, geosciences are one of the least diverse of all STEM subject areas. We present results from a series of workshops held in 2022 focused on understanding the experiences of current or recent undergraduates from under-represented groups on UK geoscience degrees. The workshops focused particularly on the participants’ sense of belonging in their degree programmes. Factors that reduced participants’ sense of belonging can be broadly grouped into unfamiliarity of geosciences amongst family and friends, lack of representation in the discipline, lack of representation among/exclusion by peers, and structural barriers. We present and discuss the recommendations made by participants for strategies to tackle each of these barriers to belonging. These strategies are intended to be practical actions that individual educators can take to enhance belonging in the geosciences.